Product Market Competition and Trade Union Structure - Klaas J. Beniers; Robert A.J. Dur (Tinbergen Institute, 2003)
Trade unions tend to reduce the dispersion of wages among their members. Skilled workers may therefore have an incentive to separate from an encompassing union and organize into a separate craft union. In this paper, we examine a theoretical model to gain insight into the determinants of the number of trade unions at a firm. We show that imperfect competition in the product market may drive skilled and unskilled workers together, even though unskilled workers use their political power in the trade union to extract rents from the skilled workers. Additionally, we examine the influence of several features of production technology on trade union structure.
Keywords: J31; J51; 330; product market competition; trade union structure; wage dispersion; Gewerkschaftspolitik; Lohnstruktur; Qualifikation; Theorie